Adsorption of lead from aqueous solution by a novel carbon based adsorbent - Al-Mamun, Abdullah; Onundi, Yusuf Bamidele; Al-Khatib, Ma'an Fahmi Rashid (2010)
Lead (Pb), due to its bioaccumulation ability, has been noted to have detrimental effects on the human body affecting the metabolism, blood and kidneys (Bansal and Goyal, 2005; Bowen, 1996). It is, therefore, imperative that lead be removed from water and wastewater to protect public health and aquatic lives. Multiwall carbon nanotubes (MWCNT) were reported by Li et al. (2003) to have metal sorption capacity of 3–4 times higher than those of powder and granular activated carbon. However, membrane clogging and separation of the nanomaterials from the filtrate pose a challenge. In this work, a novel composite material consisting of carbon nanotubes (CNT) and granular activated carbon (GAC) was synthesised to solve the filtration problem in a static filter. Various percentages of nickel (1%, 3%, 5 and 7%) were used as substrate catalyst during production of the adsorbent and these were linked to the morphology and adsorption capacity of the novel material in lead adsorption. Analyses showed that increased nickel content in the substrate from 1% to 7%, during adsorbent production, resulted in a rough surface of the CNT and increased lead removal from 24% to 89%. Equilibrium concentrations of lead for the adsorbents were achieved at about 60 minutes of contact time. The novel composite material has the potential to remove toxic materials from water and bring benefit to the society.